Gene expression and enzyme activities of the D-mannose/L-galactose pathway influence L-ascorbic acid content in Myrciaria dubia - Castro Gómez, Juan Carlos (2015)
The aim of this work was to elucidate the molecular and biochemical mechanisms that control L-ascorbic acid (AsA) content variation in Myrciaria dubia. The AsA was quantified by high-performance liquid chromatography, gene expression by real-time quantitative PCR, and enzyme activities by spectrophotometric methods from leaves and immature fruits of two genotypes (Md-60,06 and Md-02,04) with pronounced (about 2 times) differences in the AsA content. In either genotype, the fruit peel had ∼ 1.5 times more AsA than the fruit pulp and ∼ 15.0 times more than the leaf. All tissues examined demonstrated the capability for AsA biosynthesis through the D-mannose/L-galactose pathway because mRNAs of the six key genes [GDP-D-mannose pyrophosphorylase (GMP), GDP-D-mannose-3′,5′-epimerase (GME), GDP-L-galactose phosphorylase (GGP), L-galactose-1-phosphate phosphatase (GPP), L-galactose dehydrogenase (GDH), and L-galactono-1-4-lactone dehydrogenase (GLDH)] and catalytic activities of the corresponding enzymes (GMP, GDH, and GLDH) were detected. The differential expressions of genes and enzyme activities mostly correlated with the respective AsA content. Thus, the expression of several genes of the D-mannose/L-galactose pathway determined the AsA content variation in tissues of M. dubia.